Human Resource Information System (HRIS): An Important Element of Modern Organization - Lina, Manna Akter (Global Disclosure of Economics and Business, 2019)
Human resources are the most important factor for any organization working in the 21st century.  With the increasing effect of globalization and technology, organizations have started to use information systems in various functions of human resources. Human resource information system (HRIS) is not a new concept. Its application is improving day by day with changing the environment. It is one kind of software for data entry, data tracking, and other information about Human Resources like payroll, management, and accounting functions within an organization. An HRIS generally provide the ability to make the plan more effectively, control and manage HR costs; attain better efficiency and excellence in HR decision making; and improve employee and managerial productivity and effectiveness. Lastly, I can say that HRIS has various benefits, but the primary benefit is HRIS stores plenty of data about the employees of the organizations. It also helps in the strategic activities of HR managers and more in training and development, applicant tracking in recruitment and selection and human resource planning, etc.